Synthesis and characterization of N-doped TiO2 and its enhanced visible-light photocatalytic activity - Xiuwen Cheng (Arabian Journal of Chemistry, 2016)
Nitrogen doped titanium dioxide (N-TiO2) nano-photocatalysts were successfully synthesized in the presence of ammonium chloride. The resulting materials were characterized by X-ray diffraction (XRD), transmission electron microscopy (TEM), scanning electron microscopy (SEM), X-ray photoelectron spectroscopy (XPS), Fourier transform infrared spectroscopy (FTIR) and ultraviolet–visible diffuse reflection spectroscopy (UV–vis DRS). The results of XRD, SEM and TEM revealed that the as-synthesized photocatalyst was composed of spheroidal particles, which were smaller than undoped ones. XPS analysis revealed that N was effectively incorporated into the lattice of TiO2 through substituting oxygen atoms, and N might coexist in the form of substitutional N (O–Ti–N) and interstitial N (Ti–O–N). DRS exhibited that the light absorption edge red-shifted to visible region. The enhanced visible light photocatalytic activity for the degradation of RhB was mainly attributed to the smaller crystal size, more surface hydroxyl groups, stronger light absorption in visible region and narrower band gap energy.